2014
DOI: 10.4314/sajas.v44i1.1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of boar breed and season on semen parameters

Abstract: The aim of the present study was to demonstrate the influence of boar breed and season on semen parameters. The research material consisted of 31 boars: Polish Large White (PLW), Polish Landrace (PL), and Duroc × Pietrain (D × P), aged 8 to 24 months. The analysed material consisted of 1390 ejaculates, collected during the period January 2010 to October 2012. Semen samples were assessed in terms of semen volume (mL), sperm concentration (× 10 6 m/mL), total number of sperm (× 10 9 ), total number of live sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 33 publications
3
26
0
6
Order By: Relevance
“…The seasons should not affect sperm motility (Knecht et al, 2014). In our experiment, in both groups, sperm motility ranged around 70 % throughout the experiment, with daytime peak reaching 28 °C for several days.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The seasons should not affect sperm motility (Knecht et al, 2014). In our experiment, in both groups, sperm motility ranged around 70 % throughout the experiment, with daytime peak reaching 28 °C for several days.…”
Section: Discussionmentioning
confidence: 83%
“…On the contrary, during the summer months, the highest value reached in the ejaculate volume (Smital, 2008). In an experiment by Knecht et al, (2014), it has been shown that sperm concentration decreases with a higher volume of ejaculate. We cannot fully confirm this hypothesis in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…These results in conformity with data published by Ciereszko et al [9] and Trudeau and Sanford [29] , who analyzed ejaculates in relation to the season of semen collection. According to Knecht et al [6] , a high sperm concentration in ejaculates collected in winter results from lower temperatures, which has a positive effect on spermatogenesis. Auvigne [30] believes that this effect is due to the close kinship between the modern breeds of pigs and the European wild boar, for which the period of breeding activity is in late autumn and early winter, a period of a shortening length of daylight.…”
Section: The Data Presented Inmentioning
confidence: 99%
“…These include genetics, primarily the breed of the boar [5,6] . Crossbred boars, which attain sexual maturation sooner, grow faster and have a better breeding performance, as compared with pure-bred pigs, have found a wide application in artificial insemination [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Ejaculate parameters are also affected by the season of the year, ambient temperature and daylight duration, semen collection frequency, and other factors (18,30). The ejaculates of individual animals differ in physical traits and in the incidence of morphological defects in the spermatozoa (19).…”
Section: Introductionmentioning
confidence: 99%